Secretory immunological response in infants and children to parainfluenza virus types 1 and 2. - Yanagihara, R (1980)
The secretory immunological responses to natural infection with parainfluenza viruses ae not well defined. Nasopharyngeal secretion specimens from 20 infants and children naturally infected with parainfluenza virus type 1 or type 2 were examined for class-specific antibody and virus-neutralizing activity. There was a marked discordance in individual secretions between immunoglobulin A (IgA) antibody (as measured by indirect immunofluorescence) and neutralizing activity (as determined by either hemadsorption plaque or 50% tissue culture infective dose reduction) to the infecting parainfluenza virus type. Many secretions contained neutralizing activity in the absence of detectable IgA antibody; conversely, secretions with measureable IgA antibody frequently lacked neutralizing activity. Moreover, there was no relationship between neutralizing activity and the course of illness. All 11 patients with serial secretion specimens showed a fourfold or greater titer rise in IgA antibody to the homologous parainfluenza virus type. Antibody usually appeared 7 to 10 days after the onset of symptoms and peaked at about 2 weeks. This response did not appear to be related to age or to severity of illness. in general, the secretory responses resembled those seen in infants infected with respiratory syncytial virus.